Intersectionality of gender and caste in academic performance: quantitative study of an elite Indian engineering institute. (4th May 2019) - Gupta, Namrata
Abstract: Studies show that various socio-cultural statuses are not monolithic blocs; rather they intersect at various levels to create advantages or disadvantages for certain sections of any society. However, there are few studies that show how academic performance is influenced by different socio-cultural statuses of caste, class, and gender. Through a questionnaire survey of students in undergraduate engineering programs in an Indian Institute of Technology, this article explores the factors that impact the academic performance of men and women of different caste categories. The findings indicate that caste appears to be a significant indicator of academic performance although those castes with lowest economic status do not have the lowest performance. Further, gender does not have the same consequences for women and men of different castes. While men of the lowest caste have the lowest performance, it is the women of this caste that are most alienated.